(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Based on the model of steady-state heat and moisture transfer through textiles, an Inverse Problem of Bilayer Textile Materials Determination (IPTMD) under low temperature is presented. According to the idea of regularization method, the IPTMD can be formulated into a function minimization problem. Combining the finite difference algorithm for nonlinear ordinary differential equation with direct search method of one-dimensional minimization problems, an iterative algorithm for the regularized solution of the inverse problem is constructed. By analyzing the results of numerical simulation of different climate clothing, some conclusions are obtained: Hooke-Jevees direct search method can solve the inverse problem of bilayer textile materials determination, numerical simulation also shows the effectiveness of algorithm and the rationality of the proposed inverse problem, most importantly, the results can give some scientific explanations for experiments with the textile materials.